Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Strategic and Cooperative Games in Network Economics - Röhl, Nils

Signalisieren und Screening in Arbeitsmärkten - die Experimente von Brandts & Holt und Kübler et. al - Kaiser, Sarah

The challenge of assessing the market value of private companies using a standardised combination method for tax purposes--Lessons to be learnt from past experience - Müller, Jens (European Accounting Review)
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.
Keywords: Challenge of Assessing; Tax Purposes

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Behavioral Mechanisms Prompted by Badges: The Goal-Gradient Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the International Conference on Information Systems (ICIS))

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

The Hunt for Quality in a Market: Exploring the Relationship between Local Market Structure and Digitized Customer Experience - Herrmann, Philipp; Rahman, Mohammad (Workshop on Information Systems & Economics (WISE))

Modeling Languages for Business Models as Tools for Innovation: Towards a Theoretical Foundation - John, Thomas (Proceedings of the Americas' Conference on Information Systems (AMCIS))

Research on Electric Mobility in Germany: Monitoring a Commercial Battery Electric Vehicle Fleet - Görzen, Thomas; Kundisch, Dennis; Ottensmann, C.; Haubrock, A. (Proceedings of the European Electric Vehicle Congress (EEVC))

Towards a Simulation-based Approach for Evaluating Business Models for the Electric Vehicle Market - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis; Teetz, A.; Rose, M. (Proceedings of the European Electric Vehicle Congress (EEVC))

The Case for Modeling Consumer Choice Through an Adapted Total Cost of Ownership Approach - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena; Flake, S.; Freund, D.; Jung, H. (Proceedings of the European Electric Vehicle Congress (EEVC))

Providing aid to repressive terrorist source countries does not make the U.S. any safer - Gries, Thomas; Meierriecks, Daniel; Redlin, Margarete

Maritime Piracy: Socio-Economic, Political, and Institutional Determinants - Gries, Thomas; Redlin, Margarete

A Crook is a Crook ... But is He Still a Crook Abroad? On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

What is the Relationship Between Market Structure and Digitized Customer Experience? - Herrmann, Philipp; Rahman, Mohammad (INFORMS Annual Meeting)

Evaluation von Lerndesigns mit einem webbasierten Classroom Response System in der universitären Lehre - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Neugebauer, J.; Zoyke, A. (Proceedings of the 12. e-Learning Fachtagung Informatik)

Modeling Languages for Business Models as Tools for Innovation - A Systematic Review and Research Agenda - John, Thomas; Kundisch, Dennis (Tagung der Erich-Gutenberg-Arbeitsgemeinschaft Köln e.V.)

Ein TVO-Modell zur Bewertung elektrifizierter Fahrzeugflotten - Görzen, Thomas; Meier, Christian; Kundisch, Dennis (Proceedings der INFORMATIK 2014)

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Proceedings of the 22nd European Conference on Information Systems (ECIS))

Webbasierte Classroom Response Systeme in der Hochschullehre - eine eimpirische Fallstudie zur Unterstützung von Lehr-/Lernprozessen aus Studierendensicht - Zoyke, A.; Beutner, Marc; Magenheim, J.; Kundisch, Dennis; Herrmann, Philipp; Reinhardt, W. (43. dghd Jahrestagung)

Simulating Consumer Choice of Innovative Business Models for Electric Mobility - Weskamp, Christoph; John, Thomas; Suhl, Leena; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Analyzing Risk Interaction Effects among IT Projects based on Modern Portfolio Theory - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (Tagungsband der Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Competition at Last? An Economic Analysis of Current Mobile Data Roaming Regulations in Europe - Herrmann, Philipp; Kundisch, Dennis; Nicolau, V.; Zimmermann, Steffen (Multikonferenz Wirtschaftsinformatik 2014 (MKWI))

Tagungsband MKWI 2014 - Multikonferenz Wirtschaftsinformatik

Communication roles in public events: a case study on Twitter communications - Mirbabaie, Milad; Ehnis, Christian; Stieglitz, Stefan; Bunker, Deborah (Information systems and global assemblages: (re)configuring actors, artefacts, organizations: IFIP WG 8.2 Working Conference on Information Systems)

How context impacts on media choice - Stieglitz, Stefan; Brockmann, Tobias; Mirbabaie, Milad (Proceedings of the 25th Australasian Conference on Information Systems)

The role of social media network participants in extreme events - Ehnis, Christian; Mirbabaie, Milad; Bunker, Deborah; Stieglitz, Stefan (Proceedings of the 25th Australasian Conference on Information Systems)

Collective action and the common enemy effect - De Jaegher, Kris; Hoyer, Britta (Defence and Peace Economics)
How is collective defence by players affected when they face a threat from an intelligent attacker rather than a natural threat? This paper analyses this question using a game-theoretic model. Facing an intelligent attacker has an effect if players move first and visibly set their defence strategies, thereby exposing any players who do not defend, and if the attacker is, moreover, not able to commit to a random attack. Depending on the parameters of the game, the presence of an intelligent attacker either increases the probability that players jointly defend (where such joint defence either does or does not constitute a utilitarian optimum), or decreases the probability that players jointly defend (even though joint defence is a utilitarian optimum).

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth-Sloane, Caren (Business Research)

Stock Market Reactions to Customer Service Outsourcing in Manufacturing Firms - Eggert, A; Böhm, E; Cramer, C (2015 AMA Winter Marketing Educators’ Conference Proceedings)

Service transition versus service infusion: Different pathways to success for service-oriented manufacturers? - Kanuri, V; Münkhoff, E; Scheer, L. K (ISBM 2014 Academic Conference)

Selling value in business markets: Why a powerful idea often fails - Eggert, A; Haas, A; Terho, H; Ulaga, W; Münkhoff, E (ISBM 2014 Academic Conference)

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)

Service transition: A viable option for manufacturing companies with declining financial performance? - Eggert, A; Münkhoff, E; Thiesbrummel, C (Proceedings of the 43rd European Marketing Academy (EMAC) Conference)

Overcoming Roadblocks to Value-Based Selling: Aligning Organizational Support With Sales Force Activities - Terho, H; Eggert, A; Ulaga, W; Haas, A (2014 AMA Winter Marketing Educators’ Proceedings)

A Decision Support System for IT Security Incident Management - Rauchecker, Gerhard; Yasasin, Emrah; Schryen, Guido (11th International Conference on Trust, Privacy, and Security in Digital Business (TRUSTBUS))

Model-based Decision Support in Manufacturing and Service Networks - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Leena; Voß, Stefan (Business & Information Systems Engineering (BISE))

Modellbasierte Entscheidungsunterstützung in Produktions- und Service-Netzwerken - Fink, Andreas; Kliewer, Natalia; Mattfeld, Dirk; Mönch, Lars; Rothlauf, Franz; Schryen, Guido; Suhl, Lena; Voß, Stefan (Wirtschaftsinformatik)

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program

The Epistemological Impact of Literature Reviews in Information Systems Research - Schryen, Guido

Design Research zur individuellen Förderung in der beruflichen Rehabilitation - Kremer, H.-Hugo; Zoyke, A. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Ordnungsversuche als Alternative zur Einleitung - Braukmann, U.; Dilger, B.; Kremer, H.-Hugo (Wirtschaftspädagogische Handlungsfelder.Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

Forschung in Innovationsarenen - Überlegungen zu einem Paradigma im Spannungsfeld von Erkenntnis und Gestaltung - Kremer, H.-Hugo (Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

Editorial zur Ausgabe 27: Berufsorientierung - Büchter, K.; Kremer, H.-Hugo; Zoyke, A. (bwp@ Berufs- und Wirtschaftspädagogik - online)

„...Lehrer sein dagegen sehr!“ - Überlegungen im Kontext einer reflexiven Professionalisierung - Kremer, H.-Hugo; Sloane, Peter F. E. (bwp@ Berufs- und Wirtschaftspädagogik - online)

‚Übergänge mit System?!‘ - Eine Betrachtung des Übergangs- und Berufsorientierungsprozesses aus der Perspektive von Jugendlichen - Eickhoff, A.; Kremer, H.-Hugo; Zoyke, A. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Den Übergang erleben: Übergangshandeln an der Fakultät für Wirtschaftswissenschaften (Wissenschaftlicher Beitrag) - Kremer, H.-Hugo; Rüschen, E. (Zeitschrift für Hochschulentwicklung)

Einleitung - Kremer, H.-Hugo; Tramm, T.; Wilbers, K. (Kaufmännische Bildung. Sondierungen zu einer vernachlässigten Sinndimension)

Das Kaufmännische: Kaufmännische Bildung in der Ausbildungsvorbereitung - Kremer, H.-Hugo; Kallenbach, G.; Sprey, M. (Kaufmännische Bildung. Sondierungen zu einer vernachlässigten Sinndimension)

Implementing Outcome-Oriented Study Programmes at University: The Challenge of Academic Culture - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
In recent years, the design of study programmes in Higher Education (HE) has been given considerable attention by HE practitioners and researchers. Today, a sound body of concepts and experiences on different realisations of Bologna-conforming study programmes is available. The same, however, does not hold true for questions concerning the processes of implementing and further developing programmes. This paper investigates the challenges related with implementation, particularly at universities. A first aim is to understand the specifics of academic culture and their significance for programme implementation and development. Elaborating on this analysis, a second aim is to outline the role of educational developers in this process, as well as the necessary competencies to perform such a role.
Keywords: Programmentwicklung; Studienprogramme; program development; educational development; academic culture; disciplinary culture

Constitutions and Social Networks - Mauleon, Ana; Röhl, Nils; Vannetelbosch, Vincent
The objective of this paper is to analyze the formation of group structures where individuals are allowed to engage in several groups at the same time. These structures are interpreted here as social networks. Each of the groups is supposed to have specific rules or constitutions governing which members may join or leave it. A social network is then considered to be stable if none of the groups is altered any more. Given this framework, we not only analyze which influence the constitutions have on network formation but we also provide requirements under which stable networks are induced for sure. Furthermore, by embedding many-to-many matchings into our setting, we apply our model to job markets with labor unions. To some extent the unions may provide job guarantees and, therefore, have influence on the stability of the job market.

Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change - Mir Djawadi, Behnud; Fahr, Rene; Turk, Florian (Value in Health)
BackgroundMedical nonpersistence is a worldwide problem of striking magnitude. Although many fields of studies including epidemiology, sociology, and psychology try to identify determinants for medical nonpersistence, comprehensive research to explain medical nonpersistence from an economics perspective is rather scarce.ObjectivesThe aim of the study was to develop a conceptual framework that augments standard economic choice theory with psychological concepts of behavioral economics to understand how patients’ preferences for discontinuing with therapy arise over the course of the medical treatment. The availability of such a framework allows the targeted design of mechanisms for intervention strategies.MethodsOur conceptual framework models the patient as an active economic agent who evaluates the benefits and costs for continuing with therapy. We argue that a combination of loss aversion and mental accounting operations explains why patients discontinue with therapy at a specific point in time. We designed a randomized laboratory economic experiment with a student subject pool to investigate the behavioral predictions.ResultsSubjects continue with therapy as long as experienced utility losses have to be compensated. As soon as previous losses are evened out, subjects perceive the marginal benefit of persistence lower than in the beginning of the treatment. Consequently, subjects start to discontinue with therapy.ConclusionsOur results highlight that concepts of behavioral economics capture the dynamic structure of medical nonpersistence better than does standard economic choice theory. We recommend that behavioral economics should be a mandatory part of the development of possible intervention strategies aimed at improving patients’ compliance and persistence behavior.

Competitive outcomes and the inner core of NTU market games - Brangewitz, Sonja; Gamp, Jan-Philip (Economic Theory)
We consider the inner core as a solution concept for cooperative games with non-transferable utility (NTU) and its relationship to payoffs of competitive equilibria of markets that are induced by NTU games. An NTU game is an NTU market game if there exists a market such that the set of utility allocations a coalition can achieve in the market coincides with the set of utility allocations the coalition can achieve in the game. In this paper, we introduce a new construction of a market based on a closed subset of the inner core which satisfies a strict positive separability. We show that the constructed market represents the NTU game and, further, has the given closed set as the set of payoff vectors of competitive equilibria. It turns out that this market is not uniquely determined, and thus, we obtain a class of markets. Our results generalize those relating to competitive outcomes of NTU market games in the literature.

Developing study programs as a continuous task-the role of educational developers - Brahm, Taiga; Zellweger, Franziska; Jenert, Tobias; Thomann, Geri
Abstract Summary: Study programs are currently receiving more attention in Europe. In consequence, it can be observed that the roles of program development and management are professionalized. In the proposed round table, we would like to discuss the role of educational developers to support this professionalization via measures of training and process support in the light of recent developments in Switzerland. Abstract Text: Professionalization of program development as an institutional responsibility In Switzerland, different developments in higher education have led to increased attention to the development and management of the study programs such as the Bologna process, an increasingly competitive environment, the tertiarisation of a number of professions formerly acquired through vocational education. Furthermore, the national qualification framework and in particular accreditation processes require HEI to demonstrate the effectiveness of their activities (e.g., Sursock & Smit, 2010). Many different actors have been involved in development processes on the program level but also within educational development units. However, so far a systematic discourse on key issues regarding the management and development of study programs is missing, not only in German-speaking Europe. The following main question will guide the round table session: How can educational development give vital impulses for program development? Our starting points are two approaches or frameworks from Swiss HEI: a) the definition of competencies for new program professionals at the Zurich University for Teacher Education and b) a process for the strategic development of didactically-aligned study programs at the University of St. Gallen. Framework 1: Competencies for program managers The experiences with a training program for study program managers at the Zurich University for Teacher Education are reported. Over a period of four years, a competency profile has been developed and refined. Insights into the challenges and struggles of this role were gained. Despite diverse job characteristics of program managers (often resulting from an institution-specific history), there is a common set of competencies necessary to successfully cope with organizational complexity such as role competency (Schein, 1992) and lateral leadership (Kühl et al., 2005). Framework 2: Towards a systematic development of study programs The second initiative concerns the strategic approach to program development implemented at the University of St. Gallen (Brahm & Jenert, 2013; Jenert, 2011). In this structured process, the program goes through four process steps: process initiation, program analysis, program development, evaluation of the process and results. A major challenge in this process is the role of program professionals. The goal is to establish them as change agents for a didactically-aligned study program. Outcome: Role of educational development After briefly introducing the two examples, the roles of program professionals and educational development in HEI will be discussed. The questions guiding the discussion will be: • How can program development be established as a continuing task, closely tied to quality development? • How can the competencies of program professionals be developed and the local capacity and ownership be strengthened? • How can educational development support program development and provide vital impulses? Audience Engagement. Depending on the number of participants, first the questions will be discussed in groups. To put the results of the discussion on record, it will be summarized and uploaded in our weblog for further discussion after the session.
Keywords: curriculum development; study programs; Bologna; educational development; higher education

Entwicklung der Motivation von Studierenden der Wirtschafts-wissenschaften im ersten Studienjahr-eine Mixed-Methods-Studie - Jenert, Tobias; Brahm, Taiga
Das erste Studienjahr wird als wesentlicher Übergang von der Schule in die Hochschule angesehen. Im Vordergrund steht dabei häufig die Fragen der Identitätsfindung der Studierenden und das "Ankommen" im neuen Lebensabschnitt (Briggs, Clark, & Hall, 2012; Scanlon, Rowling, & Weber, 2007). In diesem Zusammenhang werden ganz unterschiedliche Aspekte untersucht, z. B. die vorhandenen Lernkompetenzen oder das Zeitmanagement der Studierenden (Barron & D'Annunzio-Green, 2009), vorhandene Einführungsprogramme an Hochschulen (z.B. Gale & Parker, 2012) oder dem ‚student engagement‘ während des ersten Jahres (Krause & Coates, 2008). Obwohl die Motivation der Studierenden als starker Prädiktor für die Leistung angesehen wird (z. B. Busato, Prins, Elshouta, & Hamaker, 2000), wurde die Motivationsentwicklung im ersten Studienjahr bis dato nur selten betrachtet. Die vorliegende Mixed Methods-Studie setzt an dieser Forschungslücke an und untersucht die Entwicklung der Studienmotivation von Wirtschaftsstudierenden im Verlauf des ersten Studienjahres. Im Rahmen einer quantitativen Längsschnittuntersuchung mit drei Messzeitpunkten wird dabei die Motivationsentwicklung über die gesamte Studierendenpopulation hinweg erfasst. Im Mittelpunkt steht die Frage, wie sich die intrinsische und extrinsische Studienmotivation sowie die studienbezogene Selbstwirksamkeit über das erste Studienjahr verändern. Zudem wird untersucht, inwiefern verschiedene studienbezogene Variablen (z. B. Angst) sich auf die Motivationsentwicklung auswirken. Um vertiefte Erkenntnisse über die Bedeutsamkeit verschiedener Gestaltungsmerkmale des ersten Studienjahres auf die Motivationsentwicklung der Studierenden zu gewinnen, wurde parallel zur quantitativen Untersuchung eine qualitative Längsschnittstudie durchgeführt mit dem Ziel, (1) verschiedene Verläufe der Motivationsentwicklung und (2) kritische Ereignisse im Eingangsjahr zu identifizieren. Das vorliegende Papier zeigt in den folgenden beiden Kapiteln den theoretischen Bezugsrahmen der Studie und die methodische Vorgehensweise. Daraufhin werden die Ergebnisse sowohl der quantitativen als auch der qualitativen Studie dargestellt und im Rahmen der Diskussion miteinander verbunden.
Keywords: Motivationsentwicklung; Hochschule; motivation; Längsschnitt; Mixed Methods

Self-Regulation and Entrepreneurial Learning - Fust, Alexander; Jenert, Tobias
Research on entrepreneurial learning often stresses the role of experience and previous knowledge. We aim to advance this perspective by pointing out the prerequisites and limitations of experience-based forms of learning and by adapting findings from educational psychology to the entrepreneurial context. Developing a model of self-regulated entrepreneurial learning (SREL) we pursue a more process oriented view of entrepreneurial learning in order to explain how learning unfolds in contexts of uncertainty and novelty when relevant experience and knowledge are scarce. The model comprises a planning, a performance and a review phase in order to support entrepreneurs in their learning process. It is suggested how SREL is related to self-efficacy, emotions and cognitive biases.
Keywords: Unternehmertum; lernen

The crucial first year: The development of students' motivation at a Business School-a Mixed Methods Study - Brahm, Taiga; Jenert, Tobias
The transition from school to university can be overwhelming for some students. While students' motivation is considered a strong predictor of performance, the development of motivation during students' transition from high school to university has rarely been investigated. Additionally, little is known about the relation of motivational aspects with other influences on study performance. The present mixed methods study addresses this research gap and examines the development of economics students' study motivation. The longitudinal mixed-method study included three waves of data collected using quantitative surveys and a series of five interviews conducted with 14 first-year students over eight months. Regarding students' development over time, the quantitative analysis showed a gradual decline in students' motivation. However, in the interviews, certain events during the first year were identified as critical incidents demotivating students. These insights into the development of students' motivation at a business school show that concrete incidents influence students' motivational development; thus, they could be transformed by structural changes.
Keywords: motivation; business school; higher education; latent growth curve model; longitudinal study; mixed methods; interview; students

Transition within higher education institutions (HEI): Differences in learning culture (LC) between first-year, bachelor, and master students at a business school - Gebhardt, Anja; Jenert, Tobias
Tertiary education comprises at least two phases, undergraduate and graduate studies. Often, the first year is regarded another, crucial phase where students familiarize with the study environment. It can be hypothesized that students' individual perceptions of learning and studying as well as the pedagogies they experience differ depending on their current study phase. Yet, differences between the phases in HE have rarely been investigated. To capture differences in student experiences in HE comprehensively, Jenert and Gebhardt (2010) have developed a framework describing Learning Culture in HEI. LC comprises a number of constructs on the three levels of the individual student, pedagogical interactions and the organization. The study first aims to quantitatively describe differences in LC between the phases of HE within a university. Based on this analysis, a second goal is to develop a deeper understanding of how students manage the transitions between different phases by applying qualitative research methods.
Keywords: Higher Education; Transitions; Bachelor; Master

Wie kann über DBR die wissenschaftliche und praktische Relevanz der Forschung gesichert werden? - Brahm, Taiga; Jenert, Tobias
Auseinandersetzungen über Forschungsmethodologien haben in den Bildungswissenschaften lange Tradition. Sie werden häufig unversöhnlich und mit Profilierung der Gegensätze geführt. Für uns hängt die Sinnhaftigkeit einer Forschungskonzeption von der Problemstellung und dem Erkenntnisinteresse ab. Dies gilt auch für Design-Based Research (DBR). Dieser Ansatz entstand als Reaktion auf die Kritik an mangelnder praktischer Anwendung von Befunden aus der empirisch-analytischen Lehr-Lernforschung. Als Ergebnis werden Theorien angestrebt, die für die Praxis einen Nutzen bieten und zugleich über die Anwendung in einer singulären Situation hinausgehen. Wir wollen folgenden Fragen nachgehen: Wo liegen die Gemeinsamkeiten, wo die Spezifika von DBR gegenüber bestehenden Methodologien? Wie wird der Generalisierungsanspruch von Theorien innerhalb von DBR verstanden und umgesetzt? Für welche Erkenntnisinteressen eignet sich DBR? Welche Methoden sind für DBR sinnvoll und können wie angewendet werden?
Keywords: design-based research; gestatlungsbasierte Forschung; Erziehungswissenschaft; Design; Mixed Methods

Verändern Medien die Lernkultur? Mögliche Rollen von Technologie zwischen virtuellen und physischen Lernräumen - Jenert, Tobias (Lernumgebungen an der Hochschule. Auf dem Weg zum Campus von morgen)

Viel Neues und doch keine Innovation!?: Fünf Thesen, warum es die Lehrentwicklung an Hochschulen schwer ha - Jenert, Tobias

Change Management in Higher Education Institutions - Brahm, Taiga; Jenert, Tobias

Modelling long-range dependence and trends in duration series: an approach based on EFARIMA and ESEMIFAR models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Statistical Papers)

On EFARIMA and ESEMIFAR Models - Beran, Jan; Feng, Yuanhua; Ghosh, Sucharita (Empirical Economic and Financial Research)

Double Conditional Smoothing of High-Frequency Volatility Surface Under a Spatial Model - Peitz, Christian; Feng, Yuanhua (Empirical Economic and Financial Research)

Data-driven estimation of diurnal patterns of durations between trades on financial markets - Feng, Yuanhua (Statistics & Probability Letters)

Data-driven estimation of realized kernels under dependent microstructure noise and further analysis using the Semi-FI-Log-ACD - Zhou, Chen; Feng, Yuanhua

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren

Der Wandel wird zur Daueraufgabe - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Revenue and profit implications of industrial service strategies - Eggert, Andreas; Hogreve, Jens; Ulaga, Wolfgang; Muenkhoff, Eva (Journal of Service Research)

"Conceptual Model and Economic Experiments to Explain Nonpersistence and Enable Mechanism Designs Fosterin Behavioral Change" - Djawadi, Behnud Mir; Fahr, Rene; Turk, Florian (Value in Health)

The Wage Effects of Social Norms-Evidence of Deviations from Peers' Body Mass in Europe - Janssen, Elmar; Fahr, Rene

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

Kaufmännische Bildung? Sondierungen zu einer vernachlässigten Sinndimension

Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag

Berufsorientierung - Büchter, K.; Kremer, H.-Hugo; Zoyke, A. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Embracing complex causality with the QCA method: An invitation - Schneider, M; Eggert, A (Journal of Business Market Management)

Differential effects of product and service innovations on the financial performance of industrial firms - Eggert, A; Thiesbrummel, C; Deutscher, C (Journal of Business Market Management)

Loyalitätswirkung des geschenkten bevorzugten Kundenstatus – Eine theoretische und empirisch-experimentelle Analyse

Der Übergang Bachelor - Master aus studentischer Perspektive: eine Rekonstruktion des Übergangshandelns als beruflicher Entwicklungspfad - Kremer, H.-Hugo; Rüschen, E. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Individuelle Bildungsgangarbeit als Antwort auf Fachkräftebedarf und Qualifikationsveränderungen - Beutner, Marc; Zoyke, A (Arbeit der Zukunft – Zukunft der Arbeit)

Bildungsgangarbeit in beruflichen Schulen – Praxisphasen und ihre Auswirkungen in der Bildungsgangarbeit - Beutner, Marc (Wirtschaftspädagogische Handlungsfelder. Festschrift für Peter F. E. Sloane zum 60. Geburtstag)

E-Learning zur Sprach- und Berufsförderung – Einblicke in AGnovel. Advanced Graphic novels in der Beruflichen Bildung - Beutner, Marc; Fortmann, M; Pechuel, R (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Entrepreneurship und Berufliche Bildung: UMW – Under my Wing – Ein Innovationsprojekt zur Unterstützung von Absolventen aus nicht geschäftsbezogenen Disziplinen bei der Unternehmensgründung - Beutner, Marc; Fortmann, L. M. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

On the Relation between Innovation and Competion: The Case of Energy Industry - Brummel, NinaMadeleine

Incorporating Reputation Information into Decision-Making Processes in Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (International Journal On Advances in Intelligent Systems (IntSys))
One goal of service-oriented computing is to realize future markets of composed services. In such markets, service providers offer services that can be ﬂexibly combined with each other. However, although crucial for decision-making, market participants are usually not able to individually estimate the quality of traded services in advance. To overcome this problem, we present a conceptual design for a reputation system that collects and processes user feedback on transactions, and provides this information as a signal for quality to participants in the market. Based on our proposed concept, we describe the incorporation of reputation information into distinct decision-making processes that are crucial in such service markets. In this context, we present a fuzzy service matching approach that takes reputation information into account. Furthermore, we introduce an adaptive service composition approach, and investigate the impact of exchanging immediate user feedback by reputation information. Last but not least, we describe the importance of reputation information for economic decisions of different market participants. The overall output of this paper is a comprehensive view on managing and exploiting reputation information in markets of composed services using the example of On-The-Fly Computing.

Horizontale Fusionen: Theorie und Praxis am Beispiel zweier Entscheidungen des Bundeskartellamtes - Eusterholz, Fabian

Gender and ethnic discrimination in hiring : evidence from field experiments in the German labor market - Kolle, Andre
The present thesis investigates the prevalence of and the reasons for hiring discrimination against women and ethnic Turks in the German labor market. Subsequent to a discussion of how to reveal discrimination, the literature on wage and employment differences inside and outside the German labor market is reviewed. Afterwards, different (economic) theories explaining inequalities in labor markets are presented. In the empirical analyses a field experiment - the so called correspondence testing - is conducted where matched pairs of (fictitious) male and female as well as German-named and Turkish-named applicants respond to, respectively, 656 and 608 (real) apprenticeship offers in predominantly male-dominated jobs. Descriptive results and econometric analyses using probit regressions on various model specifications indicate that the female applicant has a 19 percent lower callback probability compared to her male counterpart. However, differential treatment is both job- and firm-type driven. While callback rates are not statistically different from zero in female-dominated and “gender-neutral” occupations, they prevail in jobs where men are overrepresented. Furthermore, discrimination is restricted to late recruiters, i.e., companies that advertise their vacancies right before the apprenticeship is supposed to start. Similar conclusions can be drawn from the study investigating ethnic discrimination. The 32 percent lower callback probability of the Turkish-named applicant decreases if early rather than late recruiters are addressed. Apart from that, comparing response and callback rates to the candidates using different experimental designs, i.e., sending out single versus pairs of applications, yields no statistically significant differences demonstrating the unbiasedness of the correspondence approach.

Die ökonomischen Auswirkungen der Kronzeugenregelung am Beispiel des Kaffeerösterkartells - Wemhöner, Vanessa

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Vermögensteuer als Beitrag der Wohlhabenden für mehr Gleichheit - eine wirtschaftswissenschaftliche Betrachtung eines Steuerreformvorschlags - Sureth-Sloane, Caren (Wirtschaftspädagogische Handlungsfelder)

Effizienzmessung industrieller Dienstleistungen mittels Data Envelopment Analysis (ServDEA) - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Bröker, Ole; Alexander Brüne, Philipp; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans; Reichle, Florian; Wilken, Robert (Produktivität von Dienstleistungen)

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities - Kortebusch, Pia

Should Multinational Companies Request an Advance Pricing Agreement (APA) - Or Shouldn't They? - Kortebusch, Pia

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Do Investors Request Advance Tax Rulings to Alleviate Tax Risk (and do tax authorities provide them)? A Joint Taxpayers’ and Tax Authorities’ View on Investment Behavior - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Boon or Bane? Advance Tax Rulings As a Measure to Mitigate Tax Uncertainty and Foster Investment - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren